Experimental Study on the Dynamic Behavior of Running Crack Affected by Defect Shape and Filling Material - Zhen Lei; Mingsheng Zhao (Shock and Vibration)
Using the caustics method and the experimental system of digital laser dynamic caustics, the model experiment of drop hammer impact loading was carried out, and the effect of the defect shape (circular and rectangular) and the filling material (air, epoxy, and silicone rubber) on the propagation behavior of the running crack was investigated. The experimental results show that, under the impact loading, the running crack initiates at the end of precrack and propagates toward the defect. After the running crack connects to the defect, it accumulates energy within a certain period before initiating again at the upper edge of the defect. Subsequently, only one running crack is formed at the upper edge of the circular defect, but two running cracks are formed at the upper edge of the rectangular defect. The defect shape and the filling material have a significant effect not only on the energy accumulation time of the running crack at the defect but also on the stress intensity factor when initiating at the defect. The effect degree of the defect shape on the running crack propagation behavior is in the following order: circular defect > rectangular defect, whereas the effect degree of the filling material on the running crack propagation behavior follows this order: air > silicone rubber > epoxy.